DETERMINATION OF THE SOCIO-ECONOMIC IMPACT OF GULLY EROSION IN KURMIN-GWARI SETTLEMENT (FUDMA JOURNAL OF SCIENCES, 2021)
Sustainable development is the positive socio-economic change that does not undermine the ecological and social systems upon which communities and social systems are dependent. Land provides services to humans and other life forms as well as providing raw materials in production process. Land provides waste assimilation services as well as other ecosystem functions. The aim of this study is to assess the impact of gully erosion on the residents of Kurmin Gwari settlement, Kaduna State, Nigeria. The study intends to identify the percentage of the residents according to localities that have suffered socially and economically from gully incidents. It also intends to determine the relationship between adverse social and economic effects suffered by the affected people in the various localities of the study area. The Primary sources of data are direct observation from fieldwork and the use of questionnaire, while the secondary sources are topographic map and library materials. Descriptive statistical tools were applied to deal with the techniques of summarizing and describing data collected. Percentages, proportion and mean were applied to get expected frequencies. The result revealed that at Layin Pumpo 65% of respondents are affected by destruction of ancestral homeland by gully erosion. 100% are affected by loss of source of water supply. 72.5% find the gully site frightful. 92.5% experience trauma as a result of gully erosion in the area and 57.5% lost relatives. The study recommended that due to gully erosion and other natural environmental disasters, the need for an integrated environmental planning is paramount.
Keywords: Gully Erosion, Socio-Economic, Impacts, Settlement, Kurmin-Gwari